Adherence to rehabilitation and home exercise after myocardial infarction: a qualitative study of expectations, barriers and drivers - Nina Serves; Lionel Pazart; Damien Gabriel; Laurent Mourot; Fiona Ecarnot (BMC, 2023)
Abstract Background Cardiac rehabilitation is a key component of secondary prevention, but uptake is often low, and motivation to pursue exercise and lifestyle changes may be lacking in patients who have suffered from acute myocardial infarction (AMI). We explored the intentions of patients hospitalized for AMI regarding attendance at cardiac rehabilitation and the future pursuit of regular physical exercise at home. Methods We performed a qualitative study using semi-structured interviews. Eligible patients were those hospitalized for AMI in the cardiology unit of a large university hospital in Eastern France between 10/11/2021 and 7/3/2022, and who were deemed eligible for rehabilitation by the treating physician. Patients were interviewed before discharge. Interviews were transcribed and analysed by thematic analysis. We administered the Global Physical Activity Questionnaire (GPAQ) questionnaire to all participants. Results Of 17 eligible patients, 15 were interviewed, at which point saturation was reached. The majority were males (n = 13, 86%), median age 54 years (41-61). Three key themes emerged: Firstly, there is a mismatch between patients' perceptions of their physical activity and actual level of activity as assessed by objective tools. Second, cardiac rehabilitation is seen as a vector for information about the return to home after AMI. Third, regarding the intention to change lifestyle, there are persisting obstacles, drivers, fears and expectations. Conclusion Patients with AMI often overestimate how physically active they are. Even close to discharge, patients have persisting informational needs, and many see cardiac rehabilitation as a means to obtain this information, rather than as a therapeutic intervention.